Five Demands and (Not Quite) Beyond: Claim Making and Ideology in Hong Kong’s Anti-Extradition Bill Movement - LEE, FRANCIS L. F.; TANG, GARY K. Y.; YUEN, SAMSON; CHENG, EDMUND W. (Communist and post-communist studies, 2020)
This article examines the Anti-Extradition Bill (Anti-ELAB) Movement and uses claim making and claim transformation as a window to look at ideological struggle in Hong Kong. The analysis recounts the emergence of a specific configuration of movement claims: the supplementation of the moderate “Five Demands” with the abstract slogan “Revolution of Our Times” and other, more radical demands. The development of the configuration is explained by the strategic interactions among movement actors, the state, and perceived political opportunities. The configuration is also treated as symptomatic of the situation in which “One Country, Two Systems” has lost its legitimacy and independence remains a perceived impossibility.